BUDAYA MARITIM DI PESISIR UTARA PAPUA (Maritime Culture in the Papua North Coast) - Hari Suroto; Erlin N. I. Djami (BALAI ARKEOLOGI PAPUA, 2018)
The sea has been instrumental in the life of coastal communities of northern Papua since prehistoric times to historical times. The sea becomes a source of food and a means of liaison with the outside through a series of voyages. It is interesting to do maritime archeological research on the northern coast of Papua. The purpose of this research is about the shape of maritime culture on the north coast of Papua as well as the maritime tradition on the northern coast of Papua. This research was conducted with data collection, data analysis and data interpretation. The forms of maritime culture on the north coast of Papua include livelihoods, traditional knowledge related to maritime, living equipment, and local wisdom in the preservation of maritime resources. The maritime tradition on the northern coast of Papua recognizes local wisdom in organizing, managing, utilizing and participating in conserving marine and coastal resources. ABSTRAK Laut sangat berperan dalam kehidupan masyarakat pesisir utara Papua sejak masa prasejarah hingga masa sejarah. Laut menjadi sumber dalam mendapatkan makanan serta menjadi sarana penghubung dengan luar melalui serangkaian pelayaran. Sangat menarik untuk melakukan penelitian arkeologi maritim di pantai utara Papua. Tujuan penelitian ini adalah mengenai bentuk kebudayaan maritim di pantai utara Papua serta tradisi maritim di pantai utara Papua. Penelitian ini dilakukan dengan pengumpulan data, analisis data dan interpretasi data. Bentuk kebudayaan maritim di pantai utara Papua meliputi mata pencaharian hidup, pengetahuan tradisional terkait dengan maritim, peralatan hidup, dan kearifan lokal dalam pelestarian sumberdaya maritim. Tradisi maritim di pantai utara Papua mengenal kearifan lokal dalam mengatur, mengelola, memanfaatkan serta ikut melestarikan sumber daya laut dan pesisir.